2014
DOI: 10.1590/1678-775720130468
|View full text |Cite|
|
Sign up to set email alerts
|

Erosive cola-based drinks affect the bonding to enamel surface: an in vitro study

Abstract: ObjectiveThis study aimed to assess the impact of in vitro erosion provoked by different cola-based drinks (Coke types), associated or not with toothbrushing, to bonding to enamel.Material and MethodsFifty-six bovine enamel specimens were prepared and randomly assigned into seven groups (N=8): C- Control (neither eroded nor abraded), ERO-RC: 3x/1-minute immersion in Regular Coke (RC), ERO-LC: 3x/1-minute immersion in Light Coke (LC), ERO-ZC: 3x/1-minute immersion in Zero Coke (ZC) and three other eroded groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
2
22
0
7
Order By: Relevance
“…The results of the present study was supported by Casas-Apayco et al (26) who concluded that all Cola-based drinks reduced the bond strength except for Zero Coke (ZC) as ZC has lower titrable acidity than other tested Cola based drinks. This less-erosive potential was attributed to the presence of the amino acid phenylalanine, which is provided by the hydrolysis of aspartame (artificial non-saccharide sweetener) in the presence of saliva.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of the present study was supported by Casas-Apayco et al (26) who concluded that all Cola-based drinks reduced the bond strength except for Zero Coke (ZC) as ZC has lower titrable acidity than other tested Cola based drinks. This less-erosive potential was attributed to the presence of the amino acid phenylalanine, which is provided by the hydrolysis of aspartame (artificial non-saccharide sweetener) in the presence of saliva.…”
Section: Discussionsupporting
confidence: 85%
“…2). Erosive procedure (26) Composition and chemical characteristics of each immersion media are presented in (Table 1) (27,28). Each tooth was immersed in the corresponding immersion (erosive) challenge medium three times, one minute each, with an interval of eight hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes indicate that demineralized enamel is different from sound enamel, which may lead to an unsatisfactory etching pattern and infiltration of monomers, resulting in reduced bond strength 21) . Casas et al 25) stated that immersion of a tooth in Cola decreases the bond strength between enamel and resin. On the other hand, acid-eroded enamel has a higher bond strength than that of normal enamel 26) .…”
Section: Discussionmentioning
confidence: 99%
“…Especialmente em Odontopediatria, os inúmeros estudos a cerca da prevalência de lesões não-cariosas associada com uma possível maior severidade em dentes decíduos (Al-Majed et al, 2002;Kazoullis et al, 2007;Rios et al, 2007;Kreulen et al, 2010;Murakami et al, 2011;Mantonanaki et al, 2013;Habib et al, 2013), têm despertado o interesse de pesquisas objetivando a melhor compreensão do mecanismo de formação dessas lesões e de seus possíveis tratamentos (Cruz et al, 2012;Zimmerli et al, 2012;Flury et al, 2013;Lenzi et al, 2013;Casas-Apayco et al, 2014).…”
Section: Introductionunclassified